Mexico : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency; Payment Systems; Banking Supervision; Securities Regulation; and Insurance Supervision. (IMF Staff Country Reports; Country Report, 2001)
This report reviews the main laws and regulations governing the Mexican financial system, and analyzes the financial system stability in Mexico. The study assesses the implementation of macroeconomic policies, the process of bank restructuring and consolidation, and sectoral and infrastructure factors. The paper also highlights the Observance of the Code of Good Practices on Transparency in Monetary and Financial Policies; Systemically Important Payment Systems; Basel Core Principle for Effective Banking Supervision; Insurance Supervisory Principles; and Objectives and Principles of Securities Regulation.